1977
DOI: 10.1038/sc.1977.15
|View full text |Cite
|
Sign up to set email alerts
|

Atlanto-axial dislocations

Abstract: Abstract. The clinical problems, treatment and results are discussed in 23 cases of atlanto-axial dislocation.Key words: Atlanto-axial dislocation.INTEREST in the subject of atlanto-axia1 injuries and affections has grown over the years. A large number of papers have been published in the last 50 years. Ac cording to Washington (1959), Bell (1830) first described a case of infective aetiology while Block1ey and Purser (1956) attributed the earliest description of traumatic cases to Corner (1907), Fritzche (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…If the spine is stable conservative measures and regular review may be appropriate. However, several authors (Sullivan et al, 1958;Masalawala, 1977) have suggested that in this situation the above measures may not be sufficient. If there are neurological signs or suspected instability operative decompression and arthrodesis is required (Fielding and Hawkins, 1977;Phillips and Hensinger, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…If the spine is stable conservative measures and regular review may be appropriate. However, several authors (Sullivan et al, 1958;Masalawala, 1977) have suggested that in this situation the above measures may not be sufficient. If there are neurological signs or suspected instability operative decompression and arthrodesis is required (Fielding and Hawkins, 1977;Phillips and Hensinger, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…4,5,9 One case was treated with transoral resection of the odontoid process and the anterior arch of C-1 with subsequent posterior fusion. 6,8 The transverse ligament must have been severely damaged, although not necessarily ruptured. Because this type of injury is associated with severe ligament injury, spontaneous reduction may have occurred, therefore eliminating the necessity of excising the odontoid process via the transoral route.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 These dislocations are often precipitated by extreme force traumas that can result in immediate mortality due to compression of the spinal cord. 1,2,6,12,14,15 Those who are fortunate enough to survive this type of injury find themselves on the opposite end of the mortality spectrum and have few if any neurological deficits directly related to the spinal column injury. 1,[3][4][5] Nontraumatic dislocations of the dens can also occur and are due to congenital defects, metastatic tumors, and inflammatory disease.…”
Section: Observationsmentioning
confidence: 99%